2013
DOI: 10.1103/physreve.87.042810
|View full text |Cite
|
Sign up to set email alerts
|

Optimal transport exponent in spatially embedded networks

Abstract: The imposition of a cost constraint for constructing the optimal navigation structure surely represents a crucial ingredient in the design and development of any realistic navigation network. Previous works have focused on optimal transport in small-world networks built from two-dimensional lattices by adding long-range connections with Manhattan length r(ij) taken from the distribution P(ij)~r(ij)(-α), where α is a variable exponent. It has been shown that, by introducing a cost constraint on the total length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 36 publications
2
50
1
Order By: Relevance
“…(1) remains an open question. Moreover the PLN is a rich structure that opens many questions in planar networks, we intend to explore in a future work the optimal ρ that maximize transport properties [24][25][26][27] in the PLN. The relation (1) was introduced to create models that express a power law distribution for the probability of finding connected node according to the distance.…”
Section: Final Remarksmentioning
confidence: 99%
“…(1) remains an open question. Moreover the PLN is a rich structure that opens many questions in planar networks, we intend to explore in a future work the optimal ρ that maximize transport properties [24][25][26][27] in the PLN. The relation (1) was introduced to create models that express a power law distribution for the probability of finding connected node according to the distance.…”
Section: Final Remarksmentioning
confidence: 99%
“…It is then claimed that this condition is optimal due to the presence of strong correlations between the structure of the long-range connections and the underlying lattice, leading to the formation of "information gradients" that allow the traveler to find the target. Later, it was shown that, by imposing a cost constraint to the long-range connections, results in α opt = d+ 1, for both local and global knowledge conditions [26].A question that naturally arises from these navigation studies is how efficient small-world networks are for transport phenomena that typically obey local conservation laws. Here we show that enhanced Laplacian flow properties can also be observed for networks built by adding long-range connections to an underlying regular lattice, in the same fashion as previously proposed for navigation through small-world geometries [24][25][26][27][28].…”
mentioning
confidence: 99%
“…Later, it was shown that, by imposing a cost constraint to the long-range connections, results in α opt = d+ 1, for both local and global knowledge conditions [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, with development of the theory of complex networks, significant advances have been made in understanding these processes. Much of the studies were concerned with the dependence of navigation on the topological characteristics of complex networks [3][4][5][6][7], ranking of nodes in terms of network navigation [8,9] and the development of random search strategies [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%